Immunogenicity, including vitiligo, and feasibility of vaccination with autologous GM-CSF-transduced tumor cells in metastatic melanoma patients - Luiten, Rosalie M; Kueter, Esther W M; Mooi, Wolter; Gallee, Maarten P W; Rankin, Elaine M; Gerritsen, Winald R; Clift, Shirley M; Nooijen, Willem J; Weder, Pauline; van de Kasteele, Willeke F; Sein, Johan; van den Berk, Paul C M; et al. (Journal of clinical oncology, 2005)
To determine the feasibility, toxicity, and immunologic effects of vaccination with autologous tumor cells retrovirally transduced with the GM-CSF gene, we performed a phase I/II vaccination study in stage IV metastatic melanoma patients. Sixty-four patients were randomly assigned to receive three vaccinations of high-dose or low-dose tumor cells at 3-week intervals. Tumor cell vaccine preparation succeeded for 56 patients (88%), but because of progressive disease, the well-tolerated vaccination was completed in only 28 patients. We analyzed the priming of T cells against melanoma antigens, MART-1, tyrosinase, gp100, MAGE-A1, and MAGE-A3 using human leukocyte antigen/peptide tetramers and functional assays. The high-dose vaccination induced the infiltration of T cells into the tumor tissue. Three of 14 patients receiving the high-dose vaccine showed an increase in MART-1- or gp100-specific T cells in the peripheral blood during vaccination. Six patients experienced disease-free survival for more than 5 years, and two of these patients developed vitiligo at multiple sites after vaccination. MART-1- and gp100-specific T cells were found infiltrating in vitiligo skin. Upon vaccination, the T cells acquired an effector phenotype and produced interferon-gamma on specific antigenic stimulation. We conclude that vaccination with GM-CSF-transduced autologous tumor cells has limited toxicity and can enhance T-cell activation against melanocyte differentiation antigens, which can lead to vitiligo. Whether the induction of autoimmune vitiligo may prolong disease-free survival of metastatic melanoma patients who are surgically rendered as having no evidence of disease before vaccination is worthy of further investigation.